2010
DOI: 10.2478/v10134-010-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Perception of dynamic facial emotional expressions in adolescents with autism spectrum disorders (ASD)

Abstract: Previous studies have shown deficits in the perception of static emotional facial expressions in individuals with autism spectrum disorders (ASD), but results are inconclusive. Possibly, using dynamic facial stimuli expressing emotions at different levels of intensities may produce more robust results, since these resemble the expression of emotions in daily life to a greater extent. 30 Young adolescents with high-functioning ASD (IQ>85) and 30 age- and intelligence-matched controls (ages between 12 and 15)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
4
14
0
Order By: Relevance
“…This group difference is in line with previous studies suggesting that dynamic information is more important for the processing of subtle emotional expressions than for intense emotional expressions (Ambadar et al, 2005;. The results of the present study are also consistent with the impaired recognition of dynamic facial expression in individuals with ASD found in previous studies (Kessels et al, 2010;Tardif et al, 2007). However, as no work has yet investigated subtle emotions in this paradigm, using RM, this is the first study to show the compromised processing of dynamic facial expressions with subtle emotions at a perceptual level.…”
Section: Discussionsupporting
confidence: 96%
See 1 more Smart Citation
“…This group difference is in line with previous studies suggesting that dynamic information is more important for the processing of subtle emotional expressions than for intense emotional expressions (Ambadar et al, 2005;. The results of the present study are also consistent with the impaired recognition of dynamic facial expression in individuals with ASD found in previous studies (Kessels et al, 2010;Tardif et al, 2007). However, as no work has yet investigated subtle emotions in this paradigm, using RM, this is the first study to show the compromised processing of dynamic facial expressions with subtle emotions at a perceptual level.…”
Section: Discussionsupporting
confidence: 96%
“…Observational studies under structured conditions have demonstrated that individuals with ASD exhibit reduced attention and emotion in response to others' dynamic facial expressions (Corona et al, 1998;Sigman et al, 1992;Yirmiya et al, 1989). However, experimental studies investigating the processing of dynamic (Gepner et al, 2001;Kessels et al, 2010;Tardif et al, 2007) and static (Adolphs et al, 2001;Ashwin et al, 2006;Braverman et al, 1989;Castelli, 2005;Celani et al, 1999;Grossman et al, 2000) facial expressions with relatively intense emotions have reported conflicting findings. Emotional communication in daily life is mainly based on dynamic facial cues.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with this finding, previous studies have suggested that dynamic presentations of facial stimuli more clearly elicited atypical behavioral patterns in individuals with ASD than did static presentations (Kessels et al 2010;Tardif et al 2007;Uono et al 2009). The result is also consistent with several neuroimaging studies reporting that individuals with ASD exhibited reduced activation in response to dynamic facial expressions compared with the control group (Pelphrey et al 2007;Sato et al 2012) in some brain regions that are thought to be the neural bases of facial mimicry (Likowski et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Functional neuroimaging studies have also found that typically developing participants exhibited increased activation in brain regions that are thought to be the neural basis of facial mimicry (Likowski et al 2012) in response to dynamic compared with static facial expressions (e.g., Kilts et al 2003;LaBar et al 2003;Sato et al 2004). In contrast, some studies have suggested that dynamic presentations of facial stimuli elicit atypical behavioral patterns in individuals with ASD more clearly than do static presentations (Kessels et al 2010;Tardif et al 2007;Uono et al 2009). Functional neuroimaging studies have demonstrated that individuals with ASD, compared with typical developing individuals, exhibited markedly reduced activation in the social brain network in response to dynamic versus static facial expressions (Pelphrey et al 2007;Sato et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because previous studies reporting impairments in social interactions tested real communication (e.g., Corona et al, 1998;Yirmiya et al, 1989), facial expressions were dynamic in those studies. Consistent with this notion, several recent studies have shown that dynamic presentations of facial stimuli more clearly elicited the abnormal behavioral patterns in individuals with ASD than did static presentations (Kessels, Spee, & Hendriks, 2010;Tardif, Lainé, Rodriguez, & Gepner, 2007;Uono, Sato, & Toichi, 2009). For example, Uono et al (2009) reported that experiments using dynamic facial expressions as stimuli revealed the facilitative effect of emotional expression on automatic gaze-triggered attentional shifts in typically developing individuals and the impairment in this regard among individuals with ASD, although such effects were not found in response to static presentations (Hietanen & Leppänen, 2003).…”
Section: Introductionmentioning
confidence: 82%